Coloniality of Power "and processes of deconstruction of the Nation-States in Latin America" (Biography for Aníbal Quijano: The Andean Don Quixote and the Pampas) (Praxis Educativa, 2020)
The global modifications and transformations suffered from modernity, as a historical construction linked to the conquest of America, constantly reissue a kind of inequity and also redistributive “blind spots” that draw “naturally” the (unequal) horizons for our existence. Starting from decolonial studies, the ethical question about those otherness denied in our history made possible an “other” path of subjective intellection: not only in relation to the founding and historical processes with which modernity unilaterally promoted its own walk, but, fundamentally, in relation to the threshold of possibilities of transformation of our present and in our future. In this way, the changes of logic that allow granting new meanings take precisely the set of those alterities not taken into account by modernity and constituted from that “non-identity” as “the decolonial engine of History”. Trying to review the known and rename the everyday, through theoretical-political categories that challenge our colonial history, will contribute to understanding the current insistence of the coloniality of power; and, at the same time, contextualize the emergence of certain political, social, educational and cultural practices that erupt unprecedentedly, giving rise to new processes of “deconstruction” of the Nation-States in order to counteract it.
Keywords: coloniality of power; decolonial thought; deconstruction; Nation-States; Latin America.